ANALISIS EFISIENSI PRODUKSI DAN PENDAPATAN USAHATANI PADI SAWAH PADA LAHAN IRIGASI TEKNIS DAN LAHAN TADAH HUJAN DI KABUPATEN LAMPUNG SELATAN - Lidya Sari Mas Indah; Wan Abbas Zakaria; Fembriarti Erry Prasmatiwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
The aim of this research was to analyze the level of production’s efficiency  rice farming  and level of rice farming income  in the technical irrigation land and in the rainfed. The research was done in Lampung Selatan in July – September 2014. The Location of research was done in the District of Palas with consideration of the area is rice production centers in Lampung. Collection data was  by using questionnaire and interview of the samples. Samples were taken  random, consisting of 33 rice farmers in irrigation lands technical and 47 rice farmers in rainfed. Data were analyzed using frontier production function, and analysis of farm income. The results showed that : (1) differences in the level of production’s efficiency of rice farming in both types of irrigation between technical irrigation land and rainfed. The level of production’s efficiency in the planting season 1 by 76.33 percent for technical irrigation land and by 67,09 percent for rainfed. while in the planting season2  at the level of efficiency of technical irrigation land by 87, 81 percent and at rainfed by 69,26 percent. (2) Cash income of rice farmers planting season 1 and planting season 2 on technical irrigation land is greater than cash income rainfed rice farmers. Revenue in the first planting season, respectively Rp 15,276,139.75/ha for technical irrigation land and Rp14,965,568.58/ha for rainfed. In planting season 2, income is Rp15,426,044.69/ha for technical irrigation land and Rp11,672,920.22/ha for rainfed. Key words : production’s efficiency, income, technical irrigated land, the rainfed land